Kelayakan Pop up Book Sub Materi Keanekaragaman Hayati - Widianti; Syamswisna; Titin (Jurnal Ilmiah Edukatif, 2024)
The aim of this research is to determine how the media pop up in learning biology sub-material utilization of biodiversity based on the results of ethnobotany high blood pressure reduction drugs in the village of Mekar Main district of Ketapang. The technique used is with interviews, observations, and documentation which is a combination of triangulation techniques. The media validation of the pop-up book with a validator of five people, including a professor of Biology Education at FKIP University tanjungpura consisted of two people, and a teacher of biology subjects consisting of three people from different high schools/MAs. Validation analysis of pop up book media using Lawshe's formula, with 12 evaluation criteria, obtained a CVI score of 0.96 and considered valid. This means that the pop-up book media is worthy and can be used as a biology learning medium on biodiversity exploitation sub-materials.